Non-volant small mammal diversity assessment in Lata Bijih and Lata Janggut using cage trap technique. - Mohamad Faiz Mohd Zainuddin (2017)
A survey on the diversity of non-volant small mammal was conducted at two sites which are Lata Janggut and Lata Bijih, Kelantan. The main objective of this study was to determine the diversity and abundance of non-volant small mammal in both sites. 50 cage traps were used baited with banana (Musa acuminata). These traps were placed for seven days for both sites respectively. In total, 43 individuals of non-volant small mammal were recorded comprising from 10 species, three Orders and four Families namely: Muridae, Erinaceidae, Sciuridae, and Tupaiidae. The Moon rat (Echinosorex gymnura) captured was a new locality record for the Kelantan state. Continued surveys are needed because there is a need to record more data on the diversity small mammal in Kelantan.